Croissance, inégalités et pauvreté au sein des pays émergents : le cas des BRICS - Laila Porras (Revue de la Régulation)
The five countries which form the BRICS group (Brazil, Russia, India, China, and South Africa) stand out in the 2000s for their strong economic growth, linked to the economic transformation process and more specifically to the trade and financial openness, as well as to the decrease in poverty. In spite of their common evolution, we find a diversity of paths concerning the “growth-inequality” dynamics within the group. In all countries, with the exception of Brazil, growth came along with an increase in inequality. Furthermore, the rise of inequality has taken place in very different situations and according to different mechanisms. We observed the evolution of inequality is influenced by a multitude of factors. The global economic framework in which a country leads its integration into the world economy can follow various paths. According to the path taken the inequality trajectories are sometimes contrasting and widely dependent on national policies of transformation. Therefore, the effects linked to globalization cannot by themselves explain the rise or the decrease of inequality. After having described the “growth-inequality-poverty” dynamics within the BRICS from a comparative perspective, this study analyzes the evolution of the various national trajectories and proposes factors to explain the change in inequality for each country.